Sheet metal manual handling aids: Effects of design differences on muscle activity and subjective assessment - Ahmad, Nadiah; Radin Umar, Zaid @ Radin Zaid; Halim, Isa; Safitri, Dian Mardi (International Islamic University Malaysia, 2025)
Manual material handling is a common task in various industries and has been linked to work-related musculoskeletal injuries. Handling heavy and bulky sheet metal manually can cause awkward postures and forceful exertion, leading to intense biomechanical load on the workers. A trolley lifter was designed and fabricated to address this issue andimprove work postures during sheet metal transfer tasks. This study aimed to investigate the potential ergonomic benefits of the trolley lifter design compared to the traditional hydraulic table cart. Thestudy aims to determine the effect of the design differences between the two devices on muscle activities during sheet metal handling operations and to compare subjective perceptions of the subjects on these devices. The independent variable in this studywas the type of device used for sheet metal handling (i.e., trolley lifter vs. traditional hydraulic table cart) and types of sheet metals (vary by thickness). The dependent variables were muscle activities in four different muscles (biceps brachii, triceps brachii, erector spinae, and trapezius) and subjective perceptions of the devices. A randomized repeated-measureexperimental design was employed, surface electromyography was used to measure muscle activities, and a subjective questionnaire was administered to gather data on the participant'sperceptions of the devices. Participants were asked to perform separate sheet metal handling operations using both devices. The relationship between the dependent and independent variables was examined. The non-parametric test indicated that there were significant decreases in muscle activation levels in the biceps brachii, triceps brachii, erector spinae, and trapezius muscles when using the trolley lifter compared to the traditional hydraulic table cart. Moreover, participants rated the trolley lifter asmore usable, useful, and desirable than the traditional hydraulic table cart. In conclusion, the trolley lifter was a more effective and ergonomically beneficial tool for handling large sheet metals than the traditional hydraulic table cart. This study highlights the importance of ergonomic interventions in manual material handling tasks, advocating for adopting tools and equipment that can enhance worker safety, reduce physical strain, and improve overall job satisfaction.